Effect of Central-Local Governments’ Relations on Local Government Financial and Administrative Autonomy in Tanzania: A Case of Selected Municipal Councils - Mtasigazya, Paul (Journal of Advanced Research in Humanities and Social Sciences, 2024)
The fiscal and administrative decentralization have been under academic discussion and empirical knowledge is scant in local government management literature. The focus of this paper is to examine the financial and administrative deentralization and the extent and the manner in which they undermine or promote the local government autonomy in Tanzania.Therefore, this paper was guided by the following research objectives i. To examine the extent to which financial decentralization undermine or promote local government financial autonomy. ii. To explore the power of the local councils on hiring and firing staff) under administrative decentralization. This paper selected purposively a sample size of 50 respondents and data were collected through interviews and documentary reviews. The data were analysed using thematic data analysis. In this paper, the findings indicate that Central-Local Government relations have contributed to limited autonomy in financial resources and administrative matters such as recruitment, selection and the local government financial resource capacity is weak. it is recommended that the central government should cede powers to local government authorities so that they can exercise full autonomy in their areas of jurisdictions. The local government finance and administrative autonomy should be strengthened by through legal framework which empowers LGAs in financial and administrative matters.